When Traditional and Modern Culture Collide: Analysis of "Lathi" Song - Anggraheni, Dini; Fuadhiyah, Ucik; Sutopo, Bakti (Allure Journal, 2022)
A fusion of traditional and modern culture can produce a new mood in entertainment. One of the entertainment can be heard in music. As we all know, music is a form of expression that may introduce a culture. This research aimed to look at the Indonesian cultural elements in Weird Genius's song "Lathi" from various perspectives. The song "Lathi" was picked due to its widespread popularity in Indonesia, particularly on Tik Tok and Instagram. It was featured in a cover video and the Lathi Challenge, making it one of the most sought-after songs in 2020. The research outcome, a descriptive qualitative method using content analysis and semiotic approach, was employed to examine each component of the data from this song. The study's main focus was the visual, verbal, and instrumental analyses. The study's outcomes revealed a variety of cultural components in the song "Lathi" that demonstrated the song's meaning or message, especially in terms of Javanese culture.